2000
DOI: 10.1111/0022-3816.00011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Values on Consensus and Contentious Morality Policy: U.S. Death Penalty Reform, 1956-82

Abstract: We know that policy makers respond more directly to citizen values on morality policy than on nonmorality policy (Haider-Markel and Meier 1996;Mooney and Lee 1995), but how is their response different when morality policy is favored by a clear majority (consensus policy) than when public opinion is more closely divided (contentious policy) (Meier n.d.)? Which values and whose values are responded to under each of these conditions? To address these questions, we conduct an event history analysis on the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 37 publications
3
92
1
Order By: Relevance
“…As noted above, the death penalty is a morality policy and these policies are notable for their saliency (Mooney and Lee 2000). Moreover, the framing of crime issues in judicial campaigns and elsewhere probably elevated public support for the punishment independent of levels of violent crime (Baumer, Messner, and Rosenfeld 2003, 866).…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, the death penalty is a morality policy and these policies are notable for their saliency (Mooney and Lee 2000). Moreover, the framing of crime issues in judicial campaigns and elsewhere probably elevated public support for the punishment independent of levels of violent crime (Baumer, Messner, and Rosenfeld 2003, 866).…”
Section: Resultsmentioning
confidence: 99%
“…Policies related to crime and punishment are an ''easy'' issue for the public and one they tend to care a great deal about (Carmines and Stimson 1980). Issues that are less complex are characterized by higher levels of citizen participation (Gormley 1986) and have been described as ''ideal conditions for democratic responsiveness'' (Mooney and Lee 2000). The public is less likely to allow policy-makers discretion in formulating simple and highly visible policies and are more likely to invest their own time and resources into understanding and getting involved in the policy process.…”
Section: Incentives For Responsivenessmentioning
confidence: 99%
“…A new focus on measurement issues (Brace et al, 2002;Jones and Norrander, 1996;Norrander, 2001;Park, Gelman, and Bafumi, 2004) has allowed researchers to tap public attitudes about particular policies and government responsibilities in the states. Consequently, researchers have demonstrated that attitudes about narrower issues are linked to specific policies and outcomes in the states (Goggin and Wlezien, 1993;Mooney and Lee, 2000;Norrander, 2000;Putnam, 2000).…”
mentioning
confidence: 99%